2003
DOI: 10.1002/glia.10187
|View full text |Cite
|
Sign up to set email alerts
|

Surface carbonic anhydrase activity on astrocytes and neurons facilitates lactate transport

Abstract: A number of studies have provided physiological evidence for extracellular carbonic anhydrase (CA) in brain. Association of extracellular CA with glia has been limited to functional studies of gliotic slices and retinal Muller cells. While astrocytes contain intracellular CA, there has been no direct evidence for surface CA on these cells. In fact, some morphological studies suggest that the extracellular CA in brain parenchyma resides on neurons, not glia. There has been no functional demonstration of extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 30 publications
0
31
1
Order By: Relevance
“…Gradual recovery of pH i in the presence of 20 mmol/L lactate has been also observed previously in cultured astrocytes and cultured or isolated neurons. 28,29 We conclude that addition of neither pyruvate nor lactate evokes a significant intracellular acidification that could affect the interpretation of our results.…”
Section: Contribution Of Neurons and Astrocytes To The Energy Productionmentioning
confidence: 80%
“…Gradual recovery of pH i in the presence of 20 mmol/L lactate has been also observed previously in cultured astrocytes and cultured or isolated neurons. 28,29 We conclude that addition of neither pyruvate nor lactate evokes a significant intracellular acidification that could affect the interpretation of our results.…”
Section: Contribution Of Neurons and Astrocytes To The Energy Productionmentioning
confidence: 80%
“…However, it has been suggested recently that a widespread neuronal expression of CAII takes place in the brain, including the hippocampus (Wang et al, 2002). Other catalytic carbonic anhydrase isoforms in the parenchyma of the mammalian brain include the extracellular isoforms IV and XIV (Parkkila et al, 2001;Svichar and Chesler 2003) and the mitochondrial carbonic anhydrase CAV (Ghandour et al, 2000).…”
Section: Identification Of the Intrapyramidal Carbonic Anhydrase Isoformmentioning
confidence: 99%
“…In addition, it has been shown that extracellular carbonic anhydrase activity facilitates lactic acid transport in rat skeletal muscle fibers (21). In the brain CAII is highly expressed in astrocytes where it plays a supportive role in pH regulation (22) and supports the lactate shuttle from astrocytes to neurons (23).…”
mentioning
confidence: 99%